Zn2+-Ion Sensing by Fluorescent Schiff Base Calix[4]arene Macrocycles - Ullmann, Steve; Schnorr, Rene; Handke, Marcel; Laube, Christian; Abel, Bernd; Matysik, Joerg; Findeisen, Matthias; Rueger, Robert; Heine, Thomas; Kersting, Berthold (Chemistry - A European Journal, 2017)
A macrocyclic ligand (H2L) containing two o,o′-bis(iminomethyl)phenol and two calix[4]arene head units has been synthesized and its coordination chemistry towards divalent Ni and Zn investigated. The new macrocycle forms complexes of composition [ML] (M=Zn, M=Ni) and [ZnL(py)2], which were characterized by elemental analysis; IR, UV/Vis, and NMR spectroscopy; electrospray ionization mass spectrometry (ESI-MS); and X-ray crystallography (for [ZnL(py)2] and [NiL]). H2L allows the sensitive optical detection of Zn2+ among a series of biologically relevant metal ions by a dual fluorescence enhancement/quenching effect in solution. The fluorescence intensity of the macrocycle increases by a factor of ten in the presence of Zn2+ with a detection limit in the lower nanomolar region.
CRIS-Team Scopus Importer:2022-04-14
Keywords: calix[4]arenes; fluorescence sensor; macrocyclic complexes; nickel; zinc